Use of acids as additives in sugarcane silage - van Cleef, Eric H. C. B. [UNESP]; Rêgo, Anibal C.; Patiño, René M.; van Cleef, Flavia O. Scarpino [UNESP]; Ezequiel, Jane M. B. [UNESP] (Universidad de Antioquia, 2015)
Background: sugarcane silage often becomes a problem for the producers due to its high population of yeast and its high content of soluble carbohydrates. Objective: to evaluate the effect of formic and phosphoric acid on the chemical composition, fermentation characteristics, and digestibility of sugarcane silages. Methods: sugarcane was ensiled in experimental mini-silos. Five treatments were evaluated in the ensilage process (sugarcane added with 0.5 or 1% formic acid and 0.5 or 1% phosphoric acid, and a control treatment without additives). A completely randomized design was used. Results: the dry matter content of silages containing phosphoric acid was lower. Lower values of NDF, ADF, and hemicellulose were observed in the control and formic acid treatments. Conclusions: formic and phosphoric acids promote beneficial changes in the chemical composition of sugar cane silage.
Uso de ácidos como aditivos en el ensilaje de caña de azúcar
Uso de ácidos como aditivos na silagem de cana de açúcar
Keywords: Forages; Formic acid; Phosphoric acid; Saccharum officinarum